Prognostic Value of Pentraxin-3 Change After Primary Percutaneous Coronary Intervention in Patients with ST-Segment Elevation Myocardial Infarction - Li SY; Liu L; Wang DK; Ding XS; Li WP; Li HW (Dove Medical Press, 2023)
Sheng-Yu Li,1 Lei Liu,1 Ding-Kun Wang,1 Xiao-Song Ding,1 Wei-Ping Li,1,2 Hong-Wei Li1,2 1Department of Cardiology, Cardiovascular Center, Beijing Friendship Hospital, Capital Medical University, Beijing, People's Republic of China; 2Beijing Key Laboratory of Metabolic Disorder Related Cardiovascular Disease, Beijing, People's Republic of ChinaCorrespondence: Wei-Ping Li; Hong-Wei Li, Department of Cardiology, Cardiovascular Center, Beijing Friendship Hospital, Capital Medical University, No. 95 Yongan Road, Xicheng District, Beijing, 100050, People's Republic of China, Tel +86-13810267817 ; +86-13801396679, Email xueer09@163.com; lhw19656@sina.comPurpose: So far, ST-segment elevation myocardial infarction (STEMI) is still the main cause of morbidity and mortality of cardiovascular diseases worldwide. Recent studies showed that pentraxin-3 (PTX3) was related to the early diagnosis and prognosis of coronary heart disease. This study aimed to investigate the dynamical change of PTX3 after primary percutaneous coronary intervention (pPCI) in STEMI patients and its prognostic value.Patients and methods: In this prospective cohort study, a total of 350 patients were enrolled. The plasma level of PTX3 was measured at admission, 24-hour and 5-day after pPCI. The primary endpoint was the incidence of major adverse cardiac cerebral events (MACCEs) during 1-year follow-up.Results: Compared with the admission, PTX3 levels were significantly increased at 24 hours, and decreased at 5 days after pPCI in the whole cohort. PTX3 levels at these three time points were not significantly different between the patients with and without MACCEs. Notably, the change in PTX3 from admission to post-pPCI 24-hour (ΔPTX3) was higher in patients with MACCEs (112.83 vs 17.94 ng/dl, P = 0.001). The ROC curves showed that the cut-off value was 29.22 ng/dl and the area under curves was 0.622 (95% CI: 0.554- 0.690, p = 0.001). Multivariable cox regression models revealed that the high ΔPTX3 group was an independent predictor of MACCEs (adjusted HR = 2.010, 95% CI = 1.280- 3.186, p = 0.003). The higher ΔPTX3 group had significantly higher incidences of revascularization (HR = 2.094, 95% CI: 1.056- 4.150, p = 0.034) and composite MACCEs (HR = 2.219, 95% CI: 1.425- 3.454, p < 0.001). However, the change of PTX3 level from admission to post-pPCI 5-day had no independently predictive value.Conclusion: The higher increase of PTX3 level 24-hour after pPCI appeared to have a potential value in independently predicting the incidence of 1-year MACCEs in STEMI patients, especially for coronary revascularization.Keywords: pentraxin-3, primary percutaneous coronary intervention, ST-segment elevation myocardial infarction, prognosis